Model Orientasi Relasi antara Konsumen dengan Penyedia Jasa Maskapai Penerbangan Domestik - Utami, Christina Whidya; Musanto, Trisno (Jurnal Widya Manajemen & Akuntansi, 2004)
Since opening the opportunity of commercial air transport operation permit in Indonesia in the year 1999, pushing to born the various new air transport in Indonesia. Emerge the well-unbalanced between supply and demand, so that some air transport firm given on a very light emulation condition. On the other side, consumer remain to wish fulfilling standard of safety and satisfying service quality.